Modeling Spatial Patterns of Dissolved Oxygen and the Impact Mechanisms in a Cascade River - Zhong, Ming; Liu, Shanxia; Li, Kun; Jiang, Huabo; Jiang, Tao; Tang, Guoping (Frontiers in Environmental Science, 2021)
Dissolved oxygen (DO) concentration is an essential indicator for assessment of river ecosystem. A hydrodynamic and water quality mathematical model coupling one-dimensional and two-dimensional models is developed in this study, considering the characters of study area, flow velocity, temperature and organic contamination are taken as consideration in the scenario setting, the change processes of DO concentration are simulated, and their effects on DO concentration are discussed. Results indicate that: (1) A negative relation has present between DO concentration in Yongjiang River and releasing discharge of Laokou hydro-project, since reoxygenation is greater than oxygen consumption along the river, DO concentration increases from upstream to downstream. (2) DO concentration increases with the increase of releasing DO concentration, and it exhibits the different trend because of releasing BOD concentration various. (3) The increasing of water temperature results reoxygenation increases and oxygen consumption decreases, which makes DO concentration decreasing correspondingly. The study provides a scientific support for ecology operation in the cascade river, and is expect to improve the water environment by reservoir regulation.